2005
DOI: 10.1002/rcm.1820
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly process of copper cation and 2,5‐bis(3‐pyridyl)‐1,3,4‐oxadiazole under electrospray ionization conditions

Abstract: Polyhedral oligomeric silsesquioxane (POSS) polymers were synthesized by the dehydrogenative condensation of (HSiO3/2)8 with water in the presence of diethylhydroxylamine followed by trimethylsilylation. Coating films were prepared by spin‐coating of the coating solution prepared by the dehydrogenative condensation of POSS. The hardness of the coating films was evaluated using a pencil‐hardness test and was found to increase up to 8H with increases in the curing temperature. Free‐standing film and silica gel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The complexes of 2,5‐diaryl‐ and 2,5‐dipyridyl‐1,3,4‐oxadiazoles with copper were discussed in previous papers, reporting the formation of complexes of the stoichiometry 1 : 1, 2 : 1 and 2 : 2 34–36. Similar results were obtained for other metal cations, e.g.…”
Section: Resultssupporting
confidence: 67%
“…The complexes of 2,5‐diaryl‐ and 2,5‐dipyridyl‐1,3,4‐oxadiazoles with copper were discussed in previous papers, reporting the formation of complexes of the stoichiometry 1 : 1, 2 : 1 and 2 : 2 34–36. Similar results were obtained for other metal cations, e.g.…”
Section: Resultssupporting
confidence: 67%
“…17 By using a cone voltage in the range 10-80 V and a desolvation temperature 100-360°c, the ions containing two copper ions were not detected when using cu(ooccH 3 ) 2 . It has been reported that the presence of a counter ion may be of crucial importance for formation of binuclear complexes and their detection by ESI-MS. 18 In addition to cu(ooccH 3 ) 2 , the following copper salts were tested for their ability to form binuclear copper-caffeine complexes: cu(clo 4 ) 2 , cu(No 3 ) 2 , cucl 2 and cuSo 4 . Benzoic acid, 4-ntrobenzoic acid and 3,5-dinitrobenzoic acid were added to the solutions analyzed because aromatic carboxylates are common bridging agents of copper atoms in binuclear caffeine complexes.…”
Section: Resultsmentioning
confidence: 99%
“…21 It has been described that the solvent used may be of crucial importance for complexes observed in the ESI conditions. 18,22 thus, in addition to methanol, the following solvents were tested: acetonitrile, acetonitrile / methanol 1 / 1, acetonitrile/ water 1 / 1, methanol / water 1 / 1 and methanol / chloroform 1 / 1. Acetonitrile or water containing solvents were found to be inappropriate to form copper-caffeine complexes.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Therefore, sometimes in ESI mass spectra only copper(I)-containing ions are observed, whereas in the injected solution there are complexes of copper(II). [14,15] Thus it can be expected that copper(III) is very easily reduced under ESI conditions and detection of Cu(III)-containing ions is extremely difficult. However, Cu(III)-containing ions (at least formally) have been observed in ESI mass spectra.…”
mentioning
confidence: 99%